Attractiveness of Gothic villains : an exploration of sexuality and monstrosity in gothic fiction. - Tan, Faith Chew Jing. (2011)
The Gothic notion of villainy is both necessary and significant, making it very complex and elusive. Mr. Hyde, when introduced to us in the opening chapter of Robert Louis Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde, is guilty of committing a heinous crime: “[T]he man trampled calmly over the child’s body… It sounds like nothing to hear, but it was hellish to see” (Stevenson 8). Hyde’s explicit malevolence is horrifying yet unmistakably attractive. In Bram Stoker’s Dracula, Jonathan Harker displays interest over the Count through his vivid description of him. He writes in his diary: “The mouth, so far as I could see it under the heavy moustache, was fixed and rather cruel-looking, with peculiarly sharp white teeth . . .” (Stoker 25). These detailed observations of the Count hint that Jonathan is visually attracted to him despite his abnormal qualities. On the contrary, the monster in Mary Shelley’s Frankenstein exhibits a monstrous physique that is so hideous that Victor Frankenstein exclaims, “breathless horror and disgust filled my heart” (Shelley 55). Yet, Victor leaves his wife, Elizabeth, in search of the monster on his wedding-night. The characters’ strange attachment towards the three “monsters” suggests the very contradiction of danger becoming attractive. But why is that so?